Impedance Modeling and Analysis of Medium-Frequency Oscillation Caused by VSC-HVDC Connected to Local Weak Grid and DFIG-Based Wind Farms - Sun, Kun; Yao, Wei; Yan, Cai; Wen, Jinyu (Frontiers in Energy Research, 2021)
In Northwest of China, a strategy to transmit the wind-thermal-bundled power from the local grid and doubly fed induction generator (DFIG)-based wind farms through a voltage source converter-based HVDC (VSC-HVDC) can be widely applied. However, since the local grid is usually weak, a new type of electrical oscillation in the medium-frequency region may occur in the sending-end converter (SEC) of VSC-HVDC with PQ-control. The mechanism of this oscillation caused by the interaction among DFIG, local grid and SEC is not entirely understood. In this paper, the sequence impedance model of the sending end converter (SEC) of VSC-HVDC with the PQ-control outer loop and PLL is derived with the explicit analytic expression, and then the oscillation mechanism is explored based on the intuitive analysis of the system impedance frequency characteristics. Compared with the subsynchronous oscillation (SSO) caused by DFIG or power inverter, the theoretical analysis shows this medium-frequency oscillation (MFO) mainly origins from SEC due to its negative damping effect between about 100 to 200 Hz. In addition, the impact of the system controller parameters and operating condition of DFIG, local grid and SEC on the oscillation characteristics is analyzed in detail. Finally, the correctness of the theoretical analysis is validated by time-domain simulation.